The Significance of Local Earthen Heritage: An Interdisciplinary Intervention in Northern Argentina - Rivet, María Carolina (2016)
In this paper we present the rehabilitation of a historic house, and the enhancement of building techniques in earth,through a joint intervention with indigenous communities in the highlands of northern Argentina. This building, over 100 years, condenses the material history of the town of Coranzulí having been there, among other things, hisfirst school. This small village of 330 inhabitants, lies at 4000 meters abovese a level in an environment characterized by aridity. Its inhabitants, from the indigenous community atacama, are mainly pastoralists of camelids (llamas).This house was, at the time of our arrival, one of the few that were preserved as evidence of the building tradition of the area, which has been changing significantly in recent decades.This intervention has been carried out froma specific request of the native community, which on the one hand intended to revalue the local constructive heritage, and on the other hoped to have a spaceto recover the culture of the town. This house presented severe pathologies and a state of destruction of its roofs. In fact, having been for many years roofless the walls were affected by various environmental agents. However,despite this state of disrepair, its interior walls still retained some graffiti corresponding to different historical epochs.The rehabilitation work was performed with an interdisciplinary approach, involving archaeologists and architects. The ethnographic perspective allowed us to recognize the native points of view about the senses involved in this construction and its earth building techniques. At first we proceeded to record the condition of the house, basedon photographs, drawings and technical data sheets developed jointly with the community. In a second stage we proceeded to lift the wooden structure of the roof to assess the structural condition of the building, and introduced various technological innovations and structural elements to minimize the potential seismic risk. These procedures have been done through a technical proposal in accordance with local knowledge and trying not to alter the original construction system. In the third stage the roof of the house was restored,with a meticulous work of recovery of the traditional roofing techniques of straw and earth (guayado). Along this procedure several participatory workshops have been performed with the community towards the recovery of ancestral memories and local architectural practices, achieving an effective joint work.We believe that this experience is relevant to discuss not only the technical aspects of building with earth in this intervention, but also methodological aspects that are involved in working with communities that give meaning to that heritage. An approach of this kind allowsthe recognition of the diversity of building knowledge in our countries.